Trade Fundamentals: A Systematic Review - Elijah , Sunday; Zurina Hamzah, Hanny; Siong Hook, Law; Ranjanee Kaliappan, Shivee (International Journal of Psychosocial Rehabilitation, 2020)
This paper analyzed literature on trade in a systematic way. A general study of trade was conducted; the review covered several theoretical, empirical, and methodological literatures built as an attempt to overcome the concept-related measurement issues. Some of the models are largely theoretically based and wellmotivated; the most desirable status credibility test may be a detailed evaluation of the appropriateness of some of the theoretically defined fundamentals. It looked at the gravity model, HO model, computable general equilibrium, simple model of partial equilibrium, multidimensional concept of trade openness, preferential trade agreement, and Heckman’s two-stage selection method, which all have relationships with trade and are used in trade theories. It further discussed how household consumption variety is limited by distance from markets and trade restrictions; why visa restrictions could have an effect (barrier) on international trade in goods; elaborated the hypothesis that country specialization is the endogenous firm’s outcome creative response caught out-of-equilibrium through changing conditions of product and factor markets; assessed trade policy uncertainty faced by Chinese exporters to the U.S., among other reviews. The paper leads researchers to further understand the nature and structure of trade, helping to build a consistent and reliable theory framework that is applicable to academics and practitioners.